PENTINGNYA SOSIALISASI TENTANG BAHAYA NARKOTIKA PADA REMAJA DAN PELAJAR DI KOTA BONTANG - Warcipto Warcipto; Basyarudin Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research took place at BNN Bontang City, Bontang City. The aim that researchers want to achieve from the research is to provide moral support to BNN in handling the circulation of drug cases which is currently still high in the city of Bontang and also to help the younger generation not to fall into the drug cycle by using a qualitative approach with analytical literature study methods. The data used is qualitative analysis using data reduction, data presentation and conclusion drawing. The informants for this research were 2 people from the Bontang City BNN and 2 people from former drug users. The techniques used are observation, interviews and literature study. Based on data analysis of the results of interviews conducted by researchers, it was concluded that by using a combination method, namely online and manual, to improve the quality of handling drug cases in the city of Bontang, which is currently still high and of course requires extra handling.. Through this research it is hoped that it will be possible to provide education to the public, especially the younger generation, about the dangers of drugs, so that the younger generation thinks twice about using drugs. Although it is not easy because drug trafficking is massive and secretive to persuade the younger generation who are still unstable... to find their true selves. time . Even though there are several obstacles, I hope there will be synergy between BNN, law enforcement, the community and the Government joining hands to cut the chain of drug trafficking in the beloved city of Bontang. Hopefully the hopes and aspirations of making Bontang City drug free will be realized well